Expression of receptor for advanced glycosylation end products (AGEP) and inhibition of AGEP-induced cytosolic calcium elevation by diltiazem in cultured rat aortic smooth muscle cells - Zhou Qiu-Gen; Liu Nai-Feng; Xie Pei-Li (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study whether there is a high affinity receptor for advanced glycosylation end product (AGEP) on thoracic aorta smooth muscle cells (ASMC) and to test effect of diltiazem on elevation of cytosolic free calcium induced by AGEP. METHODS: Interactions of AGEP-bovine serum albumin (BSA) with ASMC were studied with radioligand binding assay and cytosolic free calcium ([Ca2+]i) was examined in cultured ASMC with Fura 2-AM. RESULTS: AGEP-BSA was specifically bound to cells at 4 degrees C and was taken up and degraded at 37 degrees C. These processes were concentration-dependent and saturable. Scatchard analysis indicated that the receptor was with dissociation constant of 65.3 +/- 1.5 nmol.L-1 and its maximal binding capacity of 1.57 +/- 0.04 nmol/g cell protein. Early glycated low density lipoprotein (LDL) was not recognized by this receptor. AGEP-BSA elevated cytosolic free calcium in a concentration-dependent manner. Pretreatment with diltiazem inhibited AGEP-BSA-induced elevation in concentration- and time-dependent manners. CONCLUSION: There was a high affinity receptor for AGEP on ASMC, which mediated internalization and degradation of AGEP. Pretreatment with diltiazem inhibited the AGEP-induced elevation of cytosolic free calcium.